Recurrent symmetrical bendings cause dwarfing in Hydrangea through spatial molecular regulation of xylem cell walls - Ley-Ngardigal, Béra; Roman, Hanaé; Brouard, Nathalie; Huché-Thélier, Lydie; Guérin, Vincent; Leduc, Nathalie (Frontiers in Plant Science, 2024)
Environmental prejudices progressively lead to the ban of dwarfing molecules in agriculture and alternatives are urgently required. Mechanical stimulation (MS) is a promising, eco-friendly and economic technique, but some responses to mechanical stimulation are varying from one plant species to others. Besides, as more frequent and violent wind episodes are forecasted under global climate change, knowledge of plant responses to stimuli mimicking wind sways is decisive for agriculture. However, little is known on plant mechanosensitive responses after long term, recurrent MS. Here, effects of 3-weeks, recurrent, symmetrical bendings (1 or 12 per day) in Hydrangea macrophylla stems are examined. Bendings repressed internodes elongation and leaf area development whereas diametrical growth of basal internode is increased. Responses were dose-dependent, and no desensitization was observed along the 3 weeks of treatment. MS was almost as much efficient as daminozide for plants dwarfing and moreover it improved stem robustness. Histological and molecular responses to MS were spatially monitored and were concordant with ongoing primary or secondary growth in the internodes. Our molecular data provide first knowledge on the molecular paths controlled by mechanical loads in Hydrangea and revealed for the first time the involvement of XYP1 in thigmomorphogenetic responses. MS had a transcriptional impact still 48h after last bending session, promoting the expression of XYP1, FLA11 and CAD1, while repressing the expression of EXP3 and XTH33 homologs respectively in accordance with xylogenesis, cell wall thickening and lignin deposition in the xylem of basal internodes. In upper elongating internodes, repression of XYP1, CAD1, SAMS1, and CDC23 homologs is correlated with ongoing primary, even though stunted, growth. For producers, our findings highlight the potential of MS as a sustainable and economical option for controlling plant compacity in Hydrangea and show valuable reinforcement of stem strength.